Behaviour and ecology of the Ethiopian wolf (Canis simensis) in a human-dominated landscape outside protected areas - Ashenafi, Z; Coulson, T; Sillero-Zubiri, C; Leader-Williams, N (2005)
The Ethiopian wolf (Canis simensis) is a very rare, endangered, endemic species surviving in isolated mountain pockets in the Ethiopian highlands, with nearly 50% of the global population living outside protected areas. In this paper we compare the ecology and behaviour of an Ethiopian wolf population living in Guassa, a communally managed area in the Central Highlands, with that of the Bale Mountains National Park in the Southern Highlands. Ethiopian wolves live at lower density in Guassa (0.2 ± 0.05/km2) than in the Bale Mountains, but giant molerats (Tachyoryctes macrocephalus), the main prey for Ethiopian wolves in Bale Mountains, do not occur in the Central Highlands. Faecal analysis identified nine prey categories across wet and dry seasons common to both populations. In total, rodents accounted for 88% of prey volume in wolf diets. Home-range size was positively related to pack size (r2 = 0.85) and there was no difference in mean home-range sizes in both areas. In Guassa, however, wolves spent less time in the presence than in the absence of humans, but wolves spent similar amounts of time in the presence and absence of cattle. These findings suggest wolves can cope with, or adapt to, the presence of livestock and people in communally managed areas. © 2005 The Zoological Society of London.